Implementation of a Mixed Strategy of Gamification and Flipped Learning in Undergraduate Basic Programming Courses - Gilberto Huesca; Gabriela Campos; Mónica Larre; Claudia Pérez-Lezama (MDPI AG, 2023)
The post-pandemic stage has accelerated the search for innovative ways that impact the teaching-learning process. Flipped learning and gamification have been used as active learning strategies to increase motivation and student learning gains. Both strategies have shown positive results when applied alone and when compared to traditional modalities. In this work, we present a quantitative study that was applied to 414 students throughout a complete course of basic programming, divided into four groups: (1) group that applied flipped learning using videos, (2) group that applied outside-class gamification, (3) group that applied both strategies, and (4) control group. A pretest-posttest process, with 96 true or false questions test, was applied to the groups to find out the normalized learning achievements of the students. A statistical analysis found that the students in groups 1 and 2 performed significantly better (+9%) than the students in the control group. In addition, the students of group 3 had a lower performance than the students of groups 1 and 2 (−10%). Our results confirm that active learning in a flipped classroom and the use of gamification can be useful and strategic tools for advancing the new way of educating in the post-pandemic period.